Оптимизация геометрии режущих элементов вооружения породоразрушающего инструмента - Ширали, И.Я. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Interaction of working parts rockdestractive tools with the rocks in the drilling work process
has been considered.
Mechanical model of loading of working parts have been made up. In accordance with corresponding
boundary and initial conditions mathematical model of the interaction process has been
developed and solved on the basis of this model. As a calculating procedure variation method of
conditional oplimizalon has been applied. As a result methods determining optimal form of working
parts providing maximum destructive power and minimum energy intensity have been developed.